Expertise in crisis the ideological contours of public scientific controversies - Caudill, David Stanley 1952- (Bristol University Press, 2024)
As the crisis of expertise continues to be a global issue, this book shows that it is not a 'scientific' controversy, but an ideological dispute with believers on both sides. If the advocates of consensus science acknowledge the uncertainties of even the best science, it is possible to open a pathway towards communication between world views
Title from publisher's bibliographic system (viewed on 18 Jan 2024)
Keywords: Science / Political aspects; Science / Public opinion; Ideology